Análise do impacto nos processos operacionais de tecnologia da informação de uma empresa do ramo financeiro adequados às exigências da lei Sarbanes-Oxley - Arrivabene, Adriano (2012)
Companies seek to develop their sustainability, daily, new business strategies encouraged by globalization. The success of these strategies ends up attracting investors as it confirms the return on their investments. In this process, information security ensures a stable foundation for business development. In the nineties the security of information did not arouse the attention required of managers, a fact that led some U.S. companies, which traded its shares on the New York Stock Exchange (NYSE) and National Association of Securities Dealers Automated Quotations (NASDAQ) were able to defraud their financial results, generating an image of stability unreal. This situation has questioned the degree of investor confidence and corporate governance worldwide. This was the motivating factor of the creation of the Sarbanes-Oxley (SOX) as a regulatory body and the integrity of information. The SOX Act required the change in the processes by means of controls and records, generating the need for many adjustments in the area of Information Technology, especially with respect to financial information. Therefore, the objective of this study was to analyze the impact of the operational procedures of Information Technology to their adaptation to the requirements of SOX Act in a company's finance arm. This goal was pursued by analyzing the information obtained by comparing the situations of various operational processes of information technology in the financial periods defined as Pre and Post SOX Act SOX Act. There was an impact on the operational processes of Information Technology with the adequacy requirements of the SOX Act.